Disney Ideas Book - Dowsett, Elizabeth (London Dorling Kindersley Ltd, 2018)
Bring your love of Disney to life with more than 100 amazing and creative projects and activities. Let your imagination run wild with Disney inspired arts and crafts, party games, puzzles, papercraft, and many more fun and practical activities. With clear, step-by-step instructions, the Disney Ideas Book guides you through each exciting activity from creating glowing BFG Dream Jars and performing a puppet show in a Jungle Book shoebox theatre, to playing skittles with the Seven Dwarfs and growing grass hair on Frozen Trolls. Featuring family favourite characters from animation and live-action movies and TV, including Frozen, Toy Story, Moana, Inside Out and Cinderella. The activities are suitable for kids and adults alike, whatever your level of ability. There are top tips on every page from expert crafters to help make your creations a success, as well as fun Disney facts to pore over. With the Disney Ideas Book, your family will never be bored again. (c) 2018 Disney/Pixar.
Include Color Illustration and Templates
Keywords: Walt Disney Productions -- Little mermaid -- Snow White and the seven dwarfs